Cohort study on correlation between serum TTF-1, PAX-8 and thyroid dysfunction after breast cancer post-operative radiation therapy - CHEN Gang, ZHANG Shunkang, GUO Shaowen, LU Yue, SUN Liyun, SHEN Lei, WANG Cheng (Zhongguo aizheng zazhi)
Background and purpose: Thyroid dysfunction can frequently be discovered in breast cancer patients during long-term follow-up after receiving post-operative radiation therapy (PORT). This study aimed to compare serum levels of thyroid transcription factors (TTFs) TTF-1 and paired box 8 (PAX-8) before and after PORT in breast cancer patients, combined with the results of serological thyroid indicators tests, and to analyze the relationship between the changes in serum levels of these two kinds of TTFs and thyroid dysfunction after breast cancer PORT. Methods: Female breast cancer patients without thyroid disease records who received PORT in Department of Radiation Oncology, Shanghai Ninth People’s Hospital Huangpu Branch, Shanghai Jiao Tong University School of Medicine from Jan. 2022 to Jun. 2022 were prospectively selected, and were divided into two groups according to being with or without supraclavicular radiation field. All the patients had given informed consent before joining the study. The study design was approved by the ethic committee of our hospital (Ethic Approval No. 2021-KY-2). Serum levels of TTF-1 and PAX-8, serological thyroid indicators [triiodothyronine (T3), tetraiodothyronine (T4), free triiodothyronine (FT3), free tetraiodothyronine (FT4), thyroid stimulating hormone (TSH) and thyroid peroxidase antibody (TPO-Ab)] were recorded before PORT, at the end of PORT, 6, 12 and 24 months after the end of PORT, respectively. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist was followed for this study. Results: Eighty patients were enrolled in this study (40 in each group). A total of 19 patients who had hypothyroidism were divided in two groups, 15 in supraclavicular field group (SC group) and 4 in non-supraclavicular field group (NSC group), respectively (P=0.004). Levels of TTF-1 [5.70 (5.11, 7.13) vs 6.68 (5.15, 7.57), P=0.296] and PAX-8 (5.26±1.01 vs 5.66±1.37, P=0.149) did not show statistically significant deference between two groups before PORT. In SC group, levels of TTF-1 and PAX-8 gradually rose in 12 months after the end of PORT. In NCS group, levels of TTF-1 and PAX-8 did not change significantly during 24 months after the end of PORT. Test results of serum TTF-1 between two groups were statistically different at 6 months [6.99 (4.73, 13.94) vs 5.79 (5.01, 6.28), P=0.049], 12 months [7.65 (5.02, 17.85) vs 5.43 (4.52, 6.22), P=0.005] after the end of PORT, while test results of serum PAX-8 between two groups were statistically different at 12 months [6.79 (4.86, 14.30) vs 5.81 (4.70,7.25), P=0.042] after the end of PORT. The median values of TTF-1 and PAX-8 test results at 12 months after the end of PORT in SC group which were both significantly higher compared with NSC group were selected as the referent thresholds. Patients in SC group whose test results were higher than referent thresholds were defined as TTF-1/PAX-8 elevating subgroups, and patients whose test results under the threshold defined as TTF-1/PAX-8 normal subgroups. The incidences of hypothyroidism were higher in elevation subgroups than in normal subgroups (65.0% vs 10.0%, 60.0% vs 15.0%, respectively, P=0.001, P=0.008, respectively). Positive correlations were observed between the elevation of TTF-1/PAX-8 at 12 months after the end of PORT and hypothyroidism after breast cancer supraclavicular field radiation (OR=9.702, 3.930, and P=0.020, 0.046, respectively) according to multivariate analysis. Conclusion: Thyroid dysfunction after breast cancer PORT was mainly manifested with hypothyroidism; supraclavicular field radiation may significantly increase the incidence of hypothyroidism; serum levels of TTF-1 and PAX-8 elevated obviously in breast cancer PORT patients who had hypothyroidism after receiving supraclavicular field radiation.